Torques and Moments of Inertia Models for Horizontal Axis Hydrokinetic Turbine Driveline - Bentes, M. H. C.; Lopes, J. J. A.; Pinheiro, K. A.; Custódio Filho, S. de S.; Vaz, J. R. P.; Mesquita, A. L. A. (Trends in Computational and Applied Mathematics, 2023)
The quantification of torques and moments of inertia of horizontal axis hydrokinetic turbine driveline is important to precisely predict the dynamic behavior of the complete system. Initially, this paper presents different models used in the literature for describing torques and moments of inertia of turbine components. A dynamic model of a small hydrokinetic turbine using belt transmission is developed. The model uses the Blade Element Momentum (BEM) for determining the power coefficient of the turbine rotor and considers the inertial effects and dissipative torques of whole system using some of the torque models and moments of inertia described previously. The results for the dynamical behavior of the turbine model are compared with experimental data, showing good agreement. In order to numerically analyze a more efficient drivetrain, the belt transmission is replaced by a planetary gearbox in the dynamic model, and the new results are also assessed. As a result, it was found that with planetary gears, a more compact transmission can be used, reducing the inertial effects, which brings a better efficiency in the starting of the machine and shortening the transient regime time.